Associations between teacher self-efficacy and teaching choice by graduate students in Engineering - Matos, Mayara da Mota [UNESP]; Iaochite, Roberto Tadeu [UNESP] (Revista Brasileira de Orientacao Profissional, 2018)
This study aimed to identify factors that influence the choice of graduate students in Engineering for teaching in higher education, teaching self-efficacy and to relate these variables. 340 postgraduate students from 33 engineering programs in Brazil participated. Pearson’s correlation between teacher self-efficacy and the dimensions of the Factors Influencing Teaching Scale showed positive correlations, indicating that as the levels of teacher self-efficacy beliefs proportionally increased, there was an increase in motivation. These results allowed us to reflect on the role of teaching experiences in graduate programs, focusing on the training of future higher education teachers.
Associações entre autoeficácia docente e escolha pela docência por pós-graduandos em Engenharia
Keywords: Graduate training; Professional choice; Self-efficacy